Association of Systemic Lupus Erythematosus with Autoimmune Hypothyroidism - Razzak, Md Abdur; Rahman, Quazi Audry Arafat; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Autoimmune disease has got tendency to co-exist with another autoimmune disease. SLE and hypothyroidism are common autoimmune diseases. They may be associated with each other. Objectives: To find the association of SLE and Autoimmune Hypothyroidism. Materials and Methods: This prospective case control study was conducted in the department of Rheumatology, CMH Dhaka from January 2017 to June 2019. Total 100 cases of SLE (Group A) were included in the study to see the presence of co-existing autoimmune hypothyroidism. Another 100 age and sex matched healthy controls without SLE (Group B) were screened for hypothyroidism. Verbal consent was taken and ethical issue was addressed. Data were collected in a pre-planned and pre-designed form after face to face interview, clinical history, physical examination and relevant laboratory investigations and plotted in tables and charts. Data were analyzed in computer SPSS Version 16. Chi-square test was done to see the level of significance. Results: Total 100 SLE patients were enrolled in this study (Group A). Age range was from 14-65. Amongst them 96 were females and only 4 were males. Majority of them belonged to 20-30 and 31-40 years age group and frequency were 40 (40%) and 35 (35%) respectively. Out of 100 SLE cases 8 patients had coexisting autoimmune hypothyroidism, 6 patients had subclinical hypothyroidism and another 4 had thyroid autoantibody with biochemically euthyroid state. Amongst the control group only 1 had hypothyroidism, 2 had subclinical hypothyroidism and 1 had thyroid autoantibody with biochemically euthyroid state. The differences in two groups were statistically significant. Conclusion: There is a strong positive association between SLE and autoimmune hypothyroidism. There are also overlapping clinical manifestations in these conditions. Therefore, thyroid screening test may be done in every case of SLE for early detection of autoimmune hypothyroidism to effectively manage both diseases. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 10-12